Longitudinal assessment of SNPs rs72552763 and rs622342 in SLC22A1 over HbA1c control among Mexican-Mestizo diabetic type 2 patients - Ortega-Ayala, Adiel; De Andrés, Fernando; Llerena, Adrián; Bartolo-Montiel, Carlos Miguel; Acosta-Altamirano, Gustavo; Molina-Guarneros, Juan Arcadio (Frontiers in Pharmacology, 2024)
Background. In Mexico, 75% of patients are not within glycaemic control criteria (HbA1c<7%), which entails a significantly variable drug response. Amongst the factors influencing this variability, are genetics, more specifically, single nucleotide polymorphisms. Three genes implied in metformin pharmacokinetics are SLC22A1, SLC22A2, and SLC22A3, which are polymorphic. While there have been cross-sectional studies on the drug response of these genes' SNPs, a longitudinal study would contribute valuable information on their effect over time. Methods. SNPs of SLC22A1, SLC22A2, and SLC22A3, were determined through PCR-TR. The clinical records of 69 patients undergoing metformin monotherapy were retrospectively assessed, metformin is the first line treatment against DMT2. A level of HbA1c<7% (time0) was considered as an inescapable inclusion criterion. Our cases were those patients who achieved HbA1c ≥7% (time1) during that period. Kaplan-Meier curves with Log-Rank test and a Cox multivariate analysis of proportional risks were performed. Aim. Determining clinical, biochemical, and genetic variables which may affect non-control (HbA1c≥7%) survival time spans amongst DT2 Mexican-Mestizo patients undergoing metformin monotherapy at HRAEI between October 2013 and December 2023. Results. 69 patients were monitored over a median period of 642 days . A comparison between time0 and time1 revealed differences in weight (p= 0.036), metformin dose mg/kg/day (p=0.003), plasmatic glucose mg/dl (p=0.048), and HbA1c (p<0.001). The median non-control survival rate was different across the 3 genotypes of rs72552763 (p=0.0034) and the dominant genotypic model GAT/GAT vs GAT/del+del/del (p=0.009). There were differences between rs622342 genotypes as well (p=0.041). In GAT/GAT the Cox model found HR=0.407 (IC95%:0.202-0.818, p=0.011) in the univariate analysis and HR=0.418 (IC95%:0.204-0.856, p=0.034) in the multivariate analysis. A/A in rs622342, reported HR=0.392 (IC95%: 0.169-0.910, p=0.029) in the multivariate analysis as well. Conclusions. Amongst DT2 Mexican-Mestizo patients undergoing metformin monotherapy the minor allele del in rs72552763 and the minor allele C in rs622342 report a significantly shorter survival median respect to the wild type variant. Patients carrying del in rs72552763 or C in rs622342 will reach non-control in less time with respect to other patients. Therefore these genotypes may constitute a therapeutic response biomarker for this population.